2020
DOI: 10.1016/j.athoracsur.2019.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared–Guided Pulmonary Segmentectomy After Endobronchial Indocyanine Green Injection

Abstract: Background. The aim of this study is to prospectively determine the feasibility and safety of near-infrared fluorescence-guided pulmonary segmentectomy after endobronchial indocyanine green (ICG) injection using virtual bronchoscopy.Methods. Fifteen patients who underwent pulmonary segmentectomy were prospectively enrolled. Using preoperative computed tomography datasets a bronchial road map was created to determine the bronchus for ICG injection. Immediately after intubation ICG was injected into the target b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Jet ventilation, in which the segment to be resected is selectively inflated, was reported by Okada et al [ 13 ]; it enables different segments to be rapidly and easily identified by inflating only the segment to be resected, but it requires the participation of an anesthesiologist and familiarity with the procedure. Transbronchial ICG administration has a similarly high reported success rate, but in addition to the proficiency required to perform bronchoscopy procedures and the danger of splashing neighbouring segments, the fact that this is an off-label procedure is also an issue [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jet ventilation, in which the segment to be resected is selectively inflated, was reported by Okada et al [ 13 ]; it enables different segments to be rapidly and easily identified by inflating only the segment to be resected, but it requires the participation of an anesthesiologist and familiarity with the procedure. Transbronchial ICG administration has a similarly high reported success rate, but in addition to the proficiency required to perform bronchoscopy procedures and the danger of splashing neighbouring segments, the fact that this is an off-label procedure is also an issue [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since this left S* segmentectomy has multiple segmental planes between the S6 and basal segment, selective ventilation via bronchoscopy is effective and useful. We previously reported near-infrared-guided pulmonary segmentectomy after endobronchial indocyanine green (ICG) injection [9]. ICG injection via the bronchus or intravenous technique is useful in S* segmentectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic surgeons have utilized ICG for determining the intersegmental plane in lung segmentectomies [33]. While intravenous ICG injection was studied initially, subsequently endobronchial injection has also been successfully attempted [34]. The authors have applied the same principle by performing nebulization of ICG for early visualization and accurate dissection of posterior membrane of trachea and bronchus in difficult tumors.…”
Section: Fluorescence Nebulization For Airway Visualizationmentioning
confidence: 99%